Reconceptualization of the Separation of Executive and Judicial Powers in the Execution of Mortgage right in Indonesia - Agustinus Phrygian Raka Anrizta (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The practice of mortgage execution in Indonesia demonstrates an overlapping authority between the executive and judicial branches of power. Article 6 of the Mortgage Law, which provides the basis for creditors to carry out parate execution directly through the KPKNL as an executive organ, conflicts with Article 224 HIR/258 RBg, which places fiat execution as a condition for executing mortgage execution. This inconsistency in norms creates uncertainty in the execution of collateral objects and obscures the principle of separation of powers, which is the foundation of the rule of law. This article aims to reanalyze the configuration of the authority relationship between the executive and the judiciary in mortgage execution, by examining the theoretical aspects of separation of powers and its application in the parate execution mechanism. Using a normative-juridical study, combining legislative, conceptual, and case-based approaches, the research finds that the dualism of execution authority creates a contradiction between the lex specialis norm and the formalistic judicial mechanism. As a result, further disputes often arise, legal protection is suboptimal for the parties, and the effectiveness of execution is hampered. A reconceptualization of the relationship between the executive and judiciary in the execution of mortgage rights is needed through harmonization and synchronization of norms, clarification of the roles of state institutions, and strengthening of preventive and repressive protection mechanisms. This reorientation is necessary to ensure that execution can proceed simply, quickly, and reliably without neglecting the proportional separation of powers in Indonesia.